Statistical Analysis of Basic Necessities and Facilities Related to Human Development Index - Javaid, Anam; Nawaz, Shahbaz; Waheed, Muhammad (Asian Journal of Social Sciences and Management Studies, 2019)
Human Development index measures the status of economy for a country. It is based on education Index, health index and on gross domestic product (GDP). Human Development index can also be seen by looking the basic necessities and facilities that are available to people in a specific area. In this research, the analysis is made on the basis of basic necessities and facilities for Multan district that people have in the specific areas. The data has been taken from MICS Survey (2007-2008) with 2892 observations. Cluster sampling is used in collecting observations. The data is collected through different developed and underdeveloped areas of the district. The purpose is to observe the availability of necessities and facilities to that area. Frequency distribution is used for assessing the facilities that people have in their homes. The results indicate that there is a great difference between availability of basic necessities and facilities between the people belonging to developed and underdeveloped areas. So by focusing these factors, the difference between the developed and underdeveloped areas can be reduced.